Hospital-Based Study of Epithelial Malignancies of Endometrial Cancer Frequency in Lahore, Pakistan, and Common Diagnostic Pitfalls. (6th January 2014) - Tanvir, Imrana; Riaz, Sabiha; Hussain, Afshan; Mehboob, Riffat; Shams, M. Usman; Khan, Haseeb Ahmad
Abstract : The current study was conducted to see the frequency of epithelial malignancies of endometrium with focus on the common diagnostic pitfalls and identify morphological and immunohistochemical markers helpful in the differential diagnosis between different subtypes. It is a retrospective descriptive study carried out on 52 specimens of endometrial tumors received in Fatima Memorial Hospital, Lahore, Pakistan, during three years (2010–2012). Patients were divided into 5 age groups: <40, 41–50, 51–60, 61–70, and >70 yrs. Tissues were fixed in 10% formalin and processed and stained with haematoxylin-eosin. Stained slides were examined to determine the histological types by WHO classification, and immunohistochemistry for WT1, p53, ER/PR, and MIB1 was done in cases where morphology alone was not helpful in making a confirmed diagnosis. 80% of specimens were of endometrioid adenocarcinomas, 11% of serous tumors, 4% of clear cell carcinoma, and 4% of squamous cell carcinomas involving both cervix and endometrium. Most of the patients (28.84%) with endometrial carcinomas fall in the age range of 51–60 yrs. Endometrioid adenocarcinoma is the most common type of epithelial endometrial malignancies. Morphology is the keystone in the evaluation of these tumors, but immunohistochemistry can also be helpful in establishing the correct diagnosis.